FINANCIAL DEVELOPMENT AND TAX REVENUES IN TURKEY: A NON-LINEAR COINTEGRATION ANALYSIS - Bayar, Yilmaz; Karamelikli, Huseyin (The European Journal of Applied Economics, 2017)
In this study, we investigated the interaction between tax revenue and major indicators of financial development including banking sector development and stock market development in Turkey using monthly data during the period January 2006 – January 2016 by employing the asymmetric ARDL cointegration method by Shin, Yu and Greenwood-Nimmo (2014). Our findings suggested that development levels of both stock market and banking sector affected total tax revenues positively when nonlinearities were considered. However, we found that there was no relationship between financial development indicators and tax revenue when nonlinearities were ignored. So, our findings demonstrated that the appropriate modelling method considering the characteristics of the dataset is important to get the right results.
Keywords: non-linear cointegration; tax revenue; banking sector development; stock market development